ABOUT OF PRACTICABILITY OF USAGE OF ANTIOXIDANT ADDITIVES IN THE PROCESS OF MEAT STUFF PULSED DISCHARGES TREATMENT - Andrey Nagdalian; Magomed Selimov; Natalya Oboturova; Yuliana Gatina (Вестник Северо-Кавказского федерального университета, 2022)
There have been studying prospects of application of food antioxidant additives like an inhibiting factor of free radicals generation while pulsed discharges treatment. In this work there was investigated the influence of electrohydraulic effect on free radicals level and lipid oxidation. The authors calculated the level of antioxidant activity of treated meat in comparison with untreated meat. Based on results of research, the authors point out inhibitor effect of used antioxidant additives.